The central vein sign in multiple sclerosis lesions: Susceptibility relaxation optimization from a routine MRI multiecho gradient echo sequence. Issue 1 (19th October 2021) - Li, Jiahao; Huang, Weiyuan; Luo, Xianfu; Wen, Yan; Cho, Junghun; Kovanlikaya, Ilhami; Gauthier, Susan A.; Nguyen, Thanh D.; Spincemaille, Pascal; Wang, Yi
Abstract: Background and Purpose: The white matter lesion central vein sign (CVS) is an emerging biomarker for multiple sclerosis (MS) differential diagnosis. Currently, CVS is detected on susceptibility weighted imaging (SWI) with suboptimal contrast. We developed an imaging method called susceptibility relaxation optimization (SRO) to improve CVS visualization. Methods: This was a retrospective study of MS patients who had MRI in June 2018 with routine 3D multiecho gradient echo (GRE) and T2‐weighted fluid‐attenuated inversion recovery (FLAIR) sequences. SRO and SWI images were reconstructed from GRE data. MS lesions were identified on FLAIR image. The CVS detection rate, the image quality score of CVS conspicuity (range 0–3), and central vein‐to‐lesion contrast were compared between SRO and SWI images. Results: In 20 MS patients (mean age 45 ± 9 years; 15 women), SRO significantly increased CVS detection rate compared to SWI (53.3%, 274/514 vs. 32.9%, 169/514; p <.001, McNemar's test). The median image quality score for SRO was 2 compared to 1 for SWI ( p <.001, Wilcoxon signed‐rank test). The median overall image quality score for SRO was 7 compared to 6 for SWI ( p = .003; Wilcoxon signed‐rank test). Central vein‐to‐lesion contrast was 0.12 ± 0.12 in SRO compared to 0.031 ± 0.075 in SWI ( p <.001, t ‐test). Conclusions: SRO yields better central vein contrast and increases CVS detection rate compared to SWI.